Mechanically activated ion channel Piezo1 modulates macrophage polarization and stiffness sensing - Hamza Atcha (Nature Portfolio, 2021)
Macrophages perform diverse functions during immune responses, but the molecular mechanisms by which physical properties of the tissue regulate macrophage behavior remain unknown. Here the authors find that Piezo1 is a mechanosensor of stiffness, and that its activity modulates macrophage polarization responses.